2022
DOI: 10.1155/2022/5563668
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Verification of Tumor Immune Microenvironment-Related Prognostic Genes in Kidney Renal Clear Cell Carcinoma

Abstract: Background. The tumor immune microenvironment is vital to kidney renal clear cell carcinoma (KIRC) progression, and immunotherapies have been shown to be effective in the management of KIRC. However, the prognostic genes associated with the tumor immune microenvironment in KIRC have not been fully identified. We obtained the KIRC RNA sequencing data and the clinical characteristics from The Cancer Genome Atlas (TCGA) and the International Cancer Genome Consortium (ICGC) database. We screened the gene modules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The extent of T-cell infiltration is remarkably high in ccRCC ( 72 ), which leads to marked inflammatory features. However, as the most abundant immune cells, CD8 + T cells display impaired anti-tumor effects, which indicates that the immune microenvironment for ccRCC is unique compared with other tumors ( 73 ). It was also reported that epigenetic modification could alter the anti-tumor immune response ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of T-cell infiltration is remarkably high in ccRCC ( 72 ), which leads to marked inflammatory features. However, as the most abundant immune cells, CD8 + T cells display impaired anti-tumor effects, which indicates that the immune microenvironment for ccRCC is unique compared with other tumors ( 73 ). It was also reported that epigenetic modification could alter the anti-tumor immune response ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current findings are consistent with previous studies, revealing a significant positive correlation between immune score and malignancy degree in patients with ccRCC in the TCGA-KIRC cohort. High immune score and ESTIMATE scores have been associated with worse prognosis ( 36 , 37 ). Additionally, the high infiltration levels of exhausted CD8 + T cells and immunosuppressive M2-like macrophages have been reported in advanced renal disease ( 8 ), suggesting that immune scores could indicate progressive T cell dysfunction in patients with ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the expression level of immune cell-related genes, the ESTIMATE algorithm was conducted to calculate the stromal score (SS), estimate score (ES), and immune score (IS) (the SS represents the level of stroma content in a tumor; the IS reflects the infiltration of immune cells in a tumor; the estimated score infers tumor purity) among the high- and low-risk groups using the “estimate” package ( 32 ). Single-sample gene set enrichment analysis (ssGSEA) was performed to calculate scores for antitumor immunity and protumor suppression for each sample ( 33 ) using “GSEABase” and “GSVA” packages.…”
Section: Methodsmentioning
confidence: 99%